Evaluasi Stabilitas Lambung Kapal 2 GT (Kapal Jukung) di Perairan Puger Berdasarkan Metode Krylov - Sudi Widodo; Hery Indria Dwi Puspita; Wazirotus Sakinah; Rudianto Rudianto; Puranggo Ganjar Widityo; Ramli Firdaus Kusnadi (STATOR: Jurnal Ilmiah Teknik Mesin, 2023)
Puger is one of the areas in Jember Regency whose main commodity comes from the sea. Fishermen need means of transportation to support them in catching fish in the sea. Puger District is also famous for its beaches and is the largest fish producer in Jember Regency. Therefore, fishing boats needed that have good performance following the characteristics of Puger waters. Puger waters have a strong trend mark with high sea currents and waves. Jukung boats are ships that are often used by fishermen in Puger. However, the process of making Jukung boats still uses conventional methods, which rely on knowledge/experience from their ancestors. The basis for making Jukung ships is mostly still not the correct procedures such as designing main dimensions, designs, and others. The impact of this affects the level of optimization of the feasibility of fishing vessels. Based on this, further studies are needed to evaluate the stability of the Jukung. This evaluation expected to be a reference regarding the level of security and comfort of the Jukung boat for the safety of the fishermen. The method used in evaluating stability is using the Krylov method. Based on the test results obtained stability are positive. so that the ship has the ability to be able to return to the even keel position after a trim/heel.